Sustainable Aquaculture Models for Coastal Communities in Indonesia: A Review of Integrated Mangrove-Shrimp Farming Systems - Muhammad Amien; Rashid Rahman; Nurul huda; Anna Dara (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. Coastal communities in Indonesia depend heavily on aquaculture for economic security, yet conventional shrimp farming practices have contributed to substantial mangrove loss, declining water quality, and reduced long-term productivity. Growing recognition of these environmental challenges has led to increasing interest in integrated mangrove–shrimp farming systems as a sustainable alternative capable of balancing ecological restoration with livelihood needs. Purpose. This review aims to evaluate existing models of integrated mangrove shrimp aquaculture in Indonesia by examining their ecological performance, economic benefits, and socio-cultural relevance for coastal communities.   Method. A qualitative research design was employed using a systematic literature review of national and international studies published between 2010 and 2024, supported by thematic analysis to identify dominant patterns and gaps. Results. The findings reveal that integrated systems particularly the silvofishery model combining mangrove restoration with semi-intensive shrimp cultivation provide measurable ecological advantages, including improved water filtration, enhanced biodiversity, and reduced disease outbreaks. Economic outcomes vary but generally demonstrate increased long-term profitability due to lower input costs and more stable yields compared to conventional monoculture farms. Social acceptance is strong in communities with existing mangrove stewardship practices, although constraints such as limited technical knowledge and unclear tenure arrangements remain significant barriers. Conclusion. The study concludes that integrated mangrove–shrimp systems offer a viable sustainability pathway for Indonesian coastal regions when supported by community training, clear land-use regulations, and targeted government incentives. These models illustrate how ecological conservation and aquaculture productivity can be mutually reinforcing within community-based resource management frameworks.